Lithium increases hippocampal SNARE protein abundance after traumatic brain injury() - Carlson, Shaun W (Exp Neurol, 2016)
Rodent models of traumatic brain injury (TBI) reproduce secondary injury sequela and cognitive impairments observed in patients afflicted by a TBI. Impaired neurotransmission has been reported in the weeks following experimental TBI, and may be a contributor to behavioral dysfunction. The soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex, the machinery facilitating vesicular docking and fusion, is a highly-conserved mechanism important for neurotransmission. Following TBI, there is a reduction in both the formation of the SNARE complex and the abundance of multiple SNARE proteins, including the chaperone protein cysteine string protein α (CSPα). Treatment with lithium in naïve rats reportedly increases the expression of CSPα. In the context of TBI, brain-injured rats treated with lithium exhibit improved outcome in published reports, but the mechanisms underlying the improvement are poorly understood. The current study evaluated the effect of lithium administration on the abundance of SNARE proteins and SNARE complex formation, hemispheric tissue loss, and neurobehavioral performance following controlled cortical impact (CCI). Sprague Dawley rats were subjected to CCI or sham injury, and treated daily with lithium chloride or vehicle for up to 14 days. Administration of lithium after TBI modestly improved spatial memory at 14 days post-injury. Semi-quantitative immunoblot analysis of hippocampal lysates revealed that treatment with lithium attenuated reductions in key SNARE proteins and SNARE complex formation at multiple time points post-injury. These findings highlight that treatment with lithium increased the abundance of synaptic proteins that facilitate neurotransmission and may contribute to improved cognitive function after TBI.